Kegagalan Diplomasi Indonesia-Arab Saudi Pada Kasus Tenaga Kerja Tuti Tursilawati - Priambodo, Dimas Bagas; Susiatiningsih, Rr. Hermini (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
The purpose of this study is to analyze the causes of the failure of Indonesian diplomacy in the Tuti Tursilawati case in Saudi Arabia by looking at various efforts made by the Indonesian government as a sending country. the concept used in this study is the concept of diplomacy in which in this concept there are several phases that must be passed to achieve the ultimate goal of problem solving, and in this study will be highlighted regarding the pre-negotiation steps that require agreement to negotiate, agreement on the negotiation agenda, and agreement procedure to be able to move to the next stage. but in the case raised in this study, the diplomatic step taken by Indonesia failed because the preconditions that were not fulfilled in the pre-negotiation phase made it difficult to bring Saudi Arabia to the negotiating table and resolve legal issues experienced by Tuti Tursilawati, until finally she was executed. died on October 29, 2018.